Voices of Mariupol-2022: cultural-anthropological profile of oral historical statements. Book review: Voices of war. Mariupol / edit. Denis Volokha; NGO "Kharkiv Human Rights Protection Group". Kharkiv: Human Rights Publishing House LLC, 2023. 276 p. - Krasikov, Dmytro (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Aim: to analyse 24 interviews included to the book «Voices of the War. Mariupol» compiled by Denys Volokha and published by CO «Kharkiv right defense group» in 2023 (276 pages) under the angle of cultural anthropology and to discover typical strategies and tactics of survival in extreme conditions of russian-Ukrainian war as well as to record the facts of actualisation of folklore consciousness and turning to Ukrainian folk culture traditions and historical experience of people who survived World War II, the famine of 1946-1947 and the hardships of the 1950s.